2020
DOI: 10.3389/fpsyg.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Online Product Presentation on the Purchase Intention of Wearable Devices: The Role of Mental Imagery and Individualism–Collectivism

Abstract: The main objective of this study was to investigate how and when online product presentation influences individual purchase intention of wearable devices in China. This study hypothesized that online product presentation would influence individual mental imagery, which, in turn, would impact purchase intention through perceived social risk and positive emotion, but this effect would be moderated by individualismcollectivism value at the individual level. We performed a laboratory experiment (2 × 2) to collect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…Because e-retailers who face too many imitators and competitors in mature homogenous markets are inclined to rely more on the help and recommendations of e-shoppers (Yi and Kim, 2017;Burnham et al, 2020). Different from offline shopping, e-shoppers are lack of real-time face-to-face interaction with salespersons, and are not able to touch, smell, taste or try on tangible goods before making a purchase (Wu et al, 2020). In addition, uncertainties in logistics distribution and the shortcoming of information leaking are on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Because e-retailers who face too many imitators and competitors in mature homogenous markets are inclined to rely more on the help and recommendations of e-shoppers (Yi and Kim, 2017;Burnham et al, 2020). Different from offline shopping, e-shoppers are lack of real-time face-to-face interaction with salespersons, and are not able to touch, smell, taste or try on tangible goods before making a purchase (Wu et al, 2020). In addition, uncertainties in logistics distribution and the shortcoming of information leaking are on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Mental imagery was measured with two items based on the research of Maier and Dost (2018), Yoo and Kim (2014), and modified to better reflect the context of this research, specifically "This video helps me imagine the use process of electric kettle in my mind, " "This video helps me visualize a trial of electric kettle." Purchase intention was measured with three items based on the research of Fu et al (2018) and Wu et al (2020), specifically "I expect to purchase the electric kettle, " "I would consider buying the electric kettle, " "The probability that I would buy the electric kettle is high." All variables were measured using Likert 7-level scales, where 1 means "strongly disagree" and 7 means "strongly agree.…”
Section: The Design Of Experimentsmentioning
confidence: 99%
“…Existing research on online product presentation videos can be divided into three categories. Studies in the first category mainly compared product presentation videos with text descriptions (Aljukhadar and Senecal, 2017 ), pictures (Park et al, 2008 ; Roggeveen et al, 2015 ; Huang et al, 2017 ; Wu et al, 2020 ; Jai et al, 2021 ), interactive images (Overmars and Poels, 2015 ), and virtual experience (Jiang and Benbasat, 2007 ; Kang et al, 2020 ; Cowan et al, 2021 ). These studies investigated the difference between the influence of product presentation videos and other presentation formats on the consumers' cognition, emotion, and behavior intention.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediating role of "telepresence, mental imagery, and predicted happiness" leads to positive influence of VR on the "behavioral intention and actual purchase." Wu et al (2020) studied the effect of product presentation on purchase intention in online retailing. They conducted an experimental study and found that the way (video and text) influences mental imagery.…”
Section: Literature Reviewmentioning
confidence: 99%